PENANGANAN BABY BLUES SYNDROME DALAM AL-QUR’AN - Irma Indriani (STIT Sunan Giri Bima, 2022)
Baby blues syndrome is a mild affective disorder syndrome, namely feelings of sadness and anxiety that often appear a few hours after delivery and peaks on day 3 to day 5 and attacks within 14 days after delivery.Some conditions can go away on their own, but other conditions, if not treated properly, will make these symptoms worse and cause Postpartum Depression, even worse, it can escalate to Postpartum Psychosis which causes the mother to hallucinate and have delusions and can hurt herself and others. others including the baby. Many people don't realize this and perceive it as a nuisance by a ghost or a mother's exaggeration. In this article, we examine the baby blues syndrome and its handling in the Qu’ran and try to ground the Qur’an in the context of daily life so that the Qur’an is not only used as meaningless reading but can be applied to solve various life problems.